P576 Therapeutic drug monitoring as predictive marker of mucosal healing in Crohn's disease patients treated with anti-TNF: a prospective multi-centre study. (25th January 2019) - Bertani, L; Bodini, G; Mondello, G; Mumolo, M G; Maltinti, S; Baldissarro, I; Tapete, G; Albano, E; Ceccarelli, L; Crespi, M; Savarino, V; Marchi, S; et al.
Abstract: Background: Anti-TNFs are currently the most commonly used drugs for Crohn's disease (CD). Therapeutic drug monitoring (TDM) is a promising strategy to optimise the healthcare resources in case of loss of response during anti-TNF treatment, yet a proactive management of TDM is being debated. The primary aim of this prospective study was to evaluate if trough levels (TL) of adalimumab (ADL) or infliximab (IFX) could be used as a marker of therapeutic response, particularly of mucosal healing (MH). The secondary aim was to evaluate if a point-of-care (POC) assay has the same results in detecting TL as an ELISA-based test. Methods: CD patients naïve to anti-TNFs who started a treatment with ADL or IFX in monotherapy in 2017 at Pisa and Genoa University Hospitals were prospectively included in this study. At Weeks 14, 22, and 54 TL were evaluated on serum samples drawn before drug administration, by using an ELISA-based test (Promonitor®, Grifols, Spain) and a POC assay (Bϋhlmann, Switzerland). At Week 54 MH (defined as the disappearance of ulcers) and clinical remission (CR) (defined as a Harvey–Bradshaw Index (HBI) <5) were evaluated. TL analysed with the two methods were correlated using Spearman's rank correlation coefficient ( r ) and the concordance between methods was assessed through Cohen's Kappa ( k ). Statistical correlation between TL and MH or CR was performed using t -test and ROC curves. Results: At the moment 35 patients (21 ADL and 14 IFX) patients were enrolled. At Week 54 MH was reached in 25 patients (71%), while CR in 28 patients (80%). A correlation between MH at Week 54 and ADL TL evaluated at Weeks 14, 22 and 54 was found ( p < 0.05, p < 0.01, p < 0.01, respectively); ROC curve at Week 22 showed the best performance, with a cut-off of 8.06 μg/ml (AUC 0.857, sensitivity 78.6%, specificity 100%). A trend of correlation between TL and MH was found for IFX, but the difference was not statistically significant. The TL values obtained with the 2 different methods showed a good correlation: r was 0.868, and k was 0.711 ( p < 0.001 for both). Conclusions: TL assessment, especially at Week 22, could be very useful in the management of CD patients naïve to anti-TNFs treated with ADL. The good correlation with MH has an important clinical implication, as far as the disappearance of ulcers should be the target of anti-TNF therapy. Moreover, POC assay has showed the same efficacy than ELISA and is quicker and easier to perform. In this perspective, a proactive management of TDM could be suggested, especially if the same results could be extended to IFX-treated patients. The study is currently ongoing, and the final results would suggest a wider use of TDM in CD patients.